Microencapsulation of omega-3 fatty acids: A review of microencapsulation and characterization methods. (December 2015) - Kaushik, Pratibha; Dowling, Kim; Barrow, Colin J.; Adhikari, Benu
Highlights: Evaluated gaps in recommended and dietary levels of omega-3 fatty acids. Reviewed the different microencapsulation techniques and wall materials. Assessed commercial viability of microencapsulation techniques and wall materials to determine the limitations of current materials. Investigated novel plant based wall materials which are postulated to deliver omega-3 fatty acids in safe and economical ways. Evaluated the characteristics of microencapsulated omega-3 fatty acids for process optimization and delivery of desired attributes. Abstract: To improve consumption of omega-3 fatty acids, foods can be enriched with omega-3 rich oils. Microencapsulation of omega-3 oils minimizes oxidative deterioration and allows their use in stable and easy-to-handle form. Microencapsulation of omega-3 fatty acids can be achieved by using a variety of methods, with the two most commonly used commercial processes being complex coacervation and spray dried emulsions. A variety of other methods are in development including spray chilling, extrusion coating and liposome entrapment. The key parameter in any of these processes is the selection of wall material. For spray dried emulsions and complex coacervates protein or polysaccharides are primarily used as shell material, although complex coacervation is currently commercially limited to gelatin. Here we review the need for microencapsulation of omega-3 oils, methods of microencapsulation and analysis, and the selection of shell material components. In particular, we discuss the method of complex coacervation, including its benefits and limitations. This review highlights the need for research on the fundamentals of interfacial and complexation behaviour of various proteins, gums and polyphenols to encapsulate and deliver omega-3 fatty acids, particularly with regard to broadening the range of shell materials that can be used in complex coacervation of omega-3 rich oils.